The discrete tanh method for solving the nonlinear differential-difference equations - Houwe, A.; İnç, Mustafa; Doka, S. Y.; Acay, B.; Hoan, L. V. C. (World Scientific Publ Co Pte Ltd, 2020)
We investigated analytical solutions for the nonlinear differential-difference equations (DDEs) having fractional-order derivative. We employed the discrete tanh method in computations. Performance of trigonometric functions, dark one solitons and rational solutions are discussed in detail. The results with reliable parameters are illustrated via 2-D and 3-D graphs.
Keywords: Discrete tanh method; differential-difference equations; solitons